Analysis of the State Budget Management System Using the SAKTI Application : A Case Study at the Maritime Affairs and Fisheries Agency of Central Sulawesi Province - Widya Widya; Sugianto Sugianto; Masruddin Masruddin; Mustamin Mustamin (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research aims to analyze the implementation of the State Institutional Financial Application System (SAKTI) in the management of the State Revenue and Expenditure Budget (APBN) at the Maritime Affairs and Fisheries Agency of Central Sulawesi Province. The primary focus of this study is to identify the benefits obtained and the challenges faced during the application process. The research method used is descriptive qualitative, with data collection techniques involving interviews, observation, and documentation. The results indicate that the implementation of the SAKTI Application has provided significant positive impacts, particularly in increasing the efficiency of financial management. This is evidenced by the acceleration of administrative processes, more systematic preparation of financial reports, and a reduction in the potential for recording errors. Furthermore, the application also supports improved transparency and accountability in budget utilization, thereby contributing to the realization of more effective, efficient, and sustainable state financial governance within the maritime and fisheries sector. Nevertheless, the research also found constraints that require serious attention, including issues related to the stability of the system and network, which is not yet optimal. This obstacle frequently hinders smooth operations, especially during periods of high workload. Therefore, an improvement in technological infrastructure and adequate technical support is necessary to ensure the application can be implemented more maximally. The findings of this research are expected to serve as a reference for policymakers in formulating strategies to enhance the quality of APBN management through the utilization of information technology in regional government agencies.